The experimental research of the electric characteristics of discharge in the quasi-steady plasma accelerator with the longitudinal magnetic field - Kozlov, A.N.; Drukarenko, S.P.; Klimov, N.S.; Moskacheva, A.A.; Podkovyrov, V.L. (Вопросы атомной науки и техники, 2009)
Installation of the coaxial quasi-steady high-current one-stage plasma accelerator with a longitudinal magnetic field
is created. The lead experiments have shown an opportunity of realization of the discharges, formation of the ionization
front and generation of the plasma streams at the presence of a longitudinal field in the accelerator channel. The currentvoltage
characteristics of the discharge at the presence and absence of a longitudinal field are measured. It is established
that a weak longitudinal field does not render the appreciable influence on the integrated characteristics of discharge in
the accelerator with the rod anode in an ion current transport regime. Створено установку коаксіального квазістаціонарного сильнострумового одноступеневого плазмового
прискорювача з подовжнім магнітним полем. Проведено експерименти, які продемонстрували можливість здійснення
розрядів, формування фронту іонізації й генерації потоків плазми за умови існування подовжнього магнітного поля в
каналі прискорювача. Виміряні вольтамперні характеристики розряду при наявності та відсутності подовжнього
поля. Встановлено, що слабке подовжнє поле не створює значного впливу на інтегральні характеристики розряду в
прискорювачі зі стрижневим анодом в режимі іонного струмопереносу. Создана установка коаксиального квазистационарного сильноточного одноступенчатого плазменного ускорителя
с продольным магнитным полем. Проведенные эксперименты продемонстрировали возможность осуществления
разрядов, формирования фронта ионизации и генерации потоков плазмы при наличии продольного поля в канале
ускорителя. Измерены вольтамперные характеристики разряда при наличии и отсутствии продольного поля.
Установлено, что слабое продольное поле не оказывает заметного влияния на интегральные характеристики разряда в
ускорителе со стрежневым анодом в режиме ионного токопереноса.